Development and validation of an automated solid-phase extraction and liquid chromatographic method for determination of lumefantrine in capillary blood on sampling paper. - Blessborn, D; Römsing, S; Annerberg, A; Sundquist, D; Björkman, A; Lindegardh, N; Bergqvist, Y (2007)
A bioanalytical method for the determination of lumefantrine in 100 microl blood applied onto sampling paper, by solid-phase extraction and liquid chromatography, has been developed and validated. Whatman 31 ET Chr sampling paper was pre-treated with 0.75 M tartaric acid before sampling capillary blood to enable a high recovery of lumefantrine. Lumefantrine was extracted from the sampling paper, then further purified using solid-phase extraction and finally quantified with HPLC. The between-day variation was below 10% over the range 0.4-25 microM. The lower limit of quantification was 0.25 microM in 100 microl capillary blood. No decrease in lumefantrine concentration in dried blood spot is seen after 4 months storage at 22 degrees C. The method was also evaluated in field samples from patients in Tanzania after treatment with lumefantrine/artemether. Lumefantrine could be estimated accurately enough to assess bioavailability and treatment compliance on day 7 (i.e. 4 days after the last dose) after a standard regimen with the lumefantrine/artemether combination.